Contextualizing Critical Care Medicine in the Face of Covid-19 Pandemic - Neupane, Harish Chandra (JNMA J Nepal Med Assoc, 2020)
Critical Care Medicine is a specialty dealing with the comprehensive management of patients having, or at risk of developing, acute, life threatening organ dysfunction. The glaring need of critical care services and human resources for critical care have become more evident in the face of the current COVID-19 Pandemic. At this juncture, when the world is facing threat to humanity with an increasing number of deaths due to COVID 19 pandemic, the discussion about the need for ICU beds and human resources for critical care management has re-surfaced and is being increasingly realized. In Nepal, as of 15(th) April, 2020, there are 194 hospitals with ICU facilities. The total ICU bed strength is 1595 in 194 hospitals (which is approximately 6% of all hospital beds) and only around 50% of them are equipped with ventilators (840). These figures indicate that Nepal has approximately 2.8 ICU beds per 100,000 population. As Nepal braces to contain a major COVID-19 outbreak, the hospital capacities of the country have already come under huge pressure. If the number of confirmed cases of COVID-19 continue to rise at the current pace, the shortage of critical care facilities will become more glaring than ever before. The current pandemic is a tremendous opportunity for health planners to accelerate action and ensure that the country is well-equipped to contain the COVID-19 pandemic. We need to be working towards infrastructure and human resource strengthening and expansion in critical care, in order to efficiently contain the pandemic.